Novel laser based on magnetic tunneling - Kadigrobov, A.; Shekhter, R.I.; Jonson, M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2005)
A new principle for a compact spin-based solid-state laser is proposed. It operates in the 1–100 THz regime, which is difficult to reach with small size lasers. Spin-flip processes in ferromagnetic conductors form a basis — the mechanism is due to a coupling of light to the exchange interaction in magnetically ordered conductors via the dependence of the exchange constant on theconduction electron momenta. The interaction strength is proportional to the large exchange energy and exceeds the Zeeman interaction by orders of magnitude. A giant lasing effect is predicted in a system where a population inversion has been created by injection of spin-polarized electrons from one ferromagnetic conductor into another through an intermediate tunnel region or weak link; the magnetizations of the two ferromagnets have different orientations. We show that thelaser frequency will be in the range 1–100 THz if the experimental data for ferromagnetic manganese perovskites with nearly 100% spin polarization are used. The optical gain is estimated to be gopt ~ 107 cm-1. This exceeds the gain of conventional semiconductor lasers by 3 or 4 orders of magnitude. An experimental configuration is proposed in order to solve heating problems at a relatively high threshold current density.